Correction: Green metrics evaluation of isoprene production by microalgae and bacteria. Issue 2 (1st December 2014) - Matos, Cristina T.; Gouveia, Luisa; Morais, Ana Rita C.; Reis, Alberto; Bogel-Łukasik, Rafał
Abstract : Correction for 'Green metrics evaluation of isoprene production by microalgae and bacteria' by Cristina T. Matos et al., Green Chem., 2013, 15, 2854–2864. Abstract : Correction for 'Green metrics evaluation of isoprene production by microalgae and bacteria' by Cristina T. Matos et al., Green Chem., 2013, 15, 2854–2864.